Information literacy in selected public and private secondary schools in Quezon City exploring school library and media specialists' roles through the lens of connectivism theory - Santos, Patrick Gabriel B.; Ramos, Alana G. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2015)
Since Information Literacy (IL) is globally considered as an essential skill for life-long learning and has recently been considered as a basic human right in the modern information society, a closer analysis on how it is being taught to students of nine selected secondary high schools in Quezon City, students in their early formative years; must be made. (Ramon Magsaysay (Cubao) High School, Quirino High School, Balara High School, Krus na Ligas High School, Quezon City High School, Ateneo de Manila High School, Miriam College High School, Diliman Preparatory School, and Claret School of Quezon City.) In light of this, an emerging paradigm, Connectivism Learning Theory was used to study the IL programs, schemes, and agenda that the schools offer and how as Information Professionals, School Library and Media Specialists' play their roles in assuring that students become information literate.
The following specific objectives were: to know, 1) what assistance are being provided by the SLMS to augment the learning gained by the student from the school; 2) what steps are being taken by the SLMS to ensure that the students and information are bridged in the most efficient way; 3) what changes are directly felt by the SLMS in the computerization of learning spaces in schools; 4) what information programs are available and how information literacy instruction can be administered effectively and efficiently by the SLMS; and 5) what defined roles of SLMS need to be strengthened considering the information use and information explosion today.
The data gathered from interviewing a total of 11 librarians and auxiliary teacher-librarians revealed that: 1) public schools do not have IL programs in place, however, a semblance of it in the form of Bibliographic Instruction is being administered inconsistently;2) private schools adhere to varying programs of teaching IL ranging from outlines of basic implementation programs to extensive schemes that aims to complement the curriculum; 3) the students on both public and private schools uniformly "Recognize" when information need is present, however, it is quickly discernible that "Locating", "Evaluating", and "Using" information is entirely different with the private school students having a higher understanding of them; and 4) the ease or difficulty of planning, implementing, and teaching IL programs is crucially hinged on the importance and priority that the school administration (also including faculty and students) grants the librarians.
Based on these findings, the study concluded that; 1) the lack of IL programs in public schools is proving to be detrimental to the goal of having skilled lifelong learners; 2) the already present digital divide is expanding more and more as private school students become more information literate through IL programs while public school students stay in the same state they are in; and 3) librarians as "information use" educators and prime movers of Information Literacy programs is directly affected by the due recognition that the school grants to the importance of their work.
Thesis (Bachelor of Library and Information Science)
Keywords: Information literacy -- Philippines -- Quezon City; Private schools -- Philippines -- Quezon City; Public schools -- Philippines -- Quezon City